Implementing content personalization strategy for Malaysian broadband service providers to enhance subscriber satisfaction - Ismail, Zahid (IEEE, 2013)
Subscriber satisfaction of a broadband service is determined by several factors such as contents delivery strategy, service infrastructure and channel packaging delivered. Currently the single-operator, single-infrastructure broadband model in Malaysia delivered by service providers such as TM UniFi cannot address the relevant and personalized contents to diversified subscribers in their needs and goals, therefore affecting the overall satisfaction of their subscribers. The objective of this research is to examine a content personalization strategy that can improve the quality of service delivered and increase the level of satisfaction of the subscribers. The content personalization strategy will allow subscriber the freedom to dynamically select any services on the network. The deployment of content personalization model to individual homes enable subscribers to personalize and customize contents based on personal preference in real-time. This delivery strategy will significantly improve customer level of experience. In the future this study will be used as input by high speed broadband service providers in analyzing methods to increase their service delivery revenue by increasing the level of subscriber satisfaction.